IDENTIFYING THE CAUSES OF SCHOOL DROPOUT IN ELEMENTARY SCHOOLS IN SUMBER DISTRICT - Asmawati, Pipit; Setyosari, Punaji; Kusumaningrum, Shirly Rizki; Indra Dewi, Radeni Sukma (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
Abstract: The problem of dropping out of school is still a challenge in the world of education in Indonesia. This study aims to identify the factors that cause students to drop out of school in three primary schools in Sumber District, Probolinggo Regency. This study used a descriptive qualitative method with a phenomenological approach to explore the social experiences and behaviors of students who dropped out of school. The research subjects included dropout students, parents, teachers, principals, and the surrounding community. Data were collected through interviews, observations, and documents and then analyzed using coding techniques. The results showed two main factors causing students to drop out of school, namely internal and external factors. Internal factors include low awareness of the importance of education, low interest in learning, and students' views on non-formal education. External factors include lack of parental support, social and environmental conditions, limited accessibility, and limited school facilities and infrastructure. This study concludes that cooperation from the government, families and communities is needed to reduce the dropout rate in Sumber District.